Quantitative skills and methods training in graduate-level education research and related fields in Ethiopia: challenges and opportunities from Addis Ababa University - O'Connell, Ann A.; Michael, Kassa; Desie, Yekoyealem; Garabed, Rebecca; Wilberforce, Winifred G. (Frontiers in Education, 2025)
BackgroundDeveloping the next generation of researchers in education and the social sciences is a primary responsibility for higher-education institutions and graduate programs in education. In low- and middle-income countries (LMICs) where resources for research training and supports may be scarce, limitations or gaps in access to training opportunities can affect graduate students' development of research and quantitative methods skills and their confidence in applying these skills to address existing and future challenges in education and related fields. These limitations have consequences for development of leaders in education research capable of identifying local priorities, strengthening education systems, and improving national-level educational outcomes.MethodsAn online survey was developed and administered to graduate students in education and related fields at Addis Ababa University (AAU) in Ethiopia. The survey was informed by a prior AAU dissertation review and a brief online survey in the United States, and focused on formal and informal training experiences, specific methods skills, and confidence in those skills. A 22-item scale was subjected to principal components analysis and used to assess skills training opportunities and confidence related to design (11 items) and analysis (11 items) aspects of quantitative methods.ResultsResults are presented for n = 44 graduate students and summarized to clarify training opportunities and curricular gaps in research and quantitative methods training. Access to formal training was lower for analysis skills (range 29.5% to 63.6%) than design skills (range 52.3% to 79.5%) (one item related to grant writing was excluded at 6.8%). Students were significantly less confident in analysis skills (p = 0.027).ConclusionOur findings highlight how access to methodology coursework, as well as disruptions due to university and school closures, can affect students' skill-building and methodological confidence. Implications for collaborative research and knowledge exchange in support of high-quality locally-prioritized and nationally-relevant research are discussed.